Do Students' Creativity and Reading Ability Influence Their Writing Ability? - Safriyani, Rizka; Anam, Syafiul (Jurnal Bahasa Inggris, 2021)
Although there have been several research attempts to identify the relationship between reading and writing skills, most of them do not address the students' creativity, mainly in Indonesian university students' context and online learning setting. This quantitative study intends to investigate the students' creativity level and the impact of students' creativity and reading on their writing skills. One hundred students completed a creativity questionnaire and online reading and writing test. Creativity styles questionnaire, reading comprehension test, and a story writing test were used to collect data. Descriptive statistics, ANCOVA, and linear regression methods were used to analyze the data. The results indicate that generally, students' creativity is high. The results also suggest a significant difference between female and male students' creativity. Furthermore, both creativity and reading ability were statistically significant to predict writing ability with the creativity scale a higher beta value than the reading scale. It can be concluded that creativity and reading ability influence students writing ability. The finding contributes to knowledge on the influential roles of creativity and reading in writing.